Unsteady natural convection in Al2O3-water nanoliquid filled in isosceles triangular enclosure with sinusoidal thermal boundary condition on bottom wall - Rahman, M. M.; Öztop, Hakan Fehmi; Mekhilef, S.; Saidur, R.; Al-Salem, Khaled (Academic Press Ltd- Elsevier Science Ltd, 2014)
Unsteady natural convection heat transfer in an isosceles triangular enclosure filled with Al2O3 nanoparticle is studied by using finite element method. The bottom of the isosceles triangular cavity is heated non-uniformly and temperature of the inclined wall is lower than that of the bottom wall. The governing parameters are Rayleigh number, solid volume fraction, aspect ratio (H/L) of the enclosure and dimensionless-time:It is found that addition of the nanoparticle into base fluid (water) affects both heat transfer and fluid flow. Heat transfer increases with addition of nanoparticle and increasing of Rayleigh number. Conduction mode of heat transfer becomes dominant for the lower values of aspect ratio. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Triangular enclosure; Nanoliquid; Unsteady natural convection; Sinusoidal thermal boundary condition